2020
DOI: 10.1021/acs.jpcc.9b11661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Central Atom and Peripheral Substituents on Photoinduced Electron Transfer in the Phthalocyanine–Fullerene Donor–Acceptor Solution-Processable Dyads

Abstract: For understanding the physical chemistry behind improving photoelectrochemical charge separation parameters and providing solution-processability, multiple peripheral substitution by 3,5-di-tert-butylphenoxy groups in design of donor−acceptor phthalocyanine−fullerene systems with two different central atoms was realized. Their UV−vis/IR/ 1 H NMR/fluorescence/femtosecond transient absorption spectra, self-assembly thermodynamics, electrochemistry, and DFT-calculated (the B3LYP+D3BJ/6-31G level of theory) geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Really not too different photoelectrochemical parameters of (ImF)CoPc(3,5-di-t BuPhO) 8 and (AcO)(ImF)MnPc(3,-5-di-t BuPhO) 8 are observed at the stability constant values of (6.60 ± 1.15) 10 5 and (3.83 ± 0.79) 10 4 L mol −1 (Figure 10, Table 12) and at the ImF bonding energy about 17.6 kcal mol −1 and about 8.7 kcal mol −1Á172 , respectively. When taking into account a lot of dispersion intermolecular interactions of bulky tert-butyl groups by dispersion correction for density functional (D3BJ), the authors [116] have shown mediating of substitution influence owing to averaging of the bonding energies of both dyads (about 44.3 kcal mol −1 ).…”
Section: The Relevance Of Mpxs For Sm-oscsmentioning
confidence: 99%
See 4 more Smart Citations
“…Really not too different photoelectrochemical parameters of (ImF)CoPc(3,5-di-t BuPhO) 8 and (AcO)(ImF)MnPc(3,-5-di-t BuPhO) 8 are observed at the stability constant values of (6.60 ± 1.15) 10 5 and (3.83 ± 0.79) 10 4 L mol −1 (Figure 10, Table 12) and at the ImF bonding energy about 17.6 kcal mol −1 and about 8.7 kcal mol −1Á172 , respectively. When taking into account a lot of dispersion intermolecular interactions of bulky tert-butyl groups by dispersion correction for density functional (D3BJ), the authors [116] have shown mediating of substitution influence owing to averaging of the bonding energies of both dyads (about 44.3 kcal mol −1 ).…”
Section: The Relevance Of Mpxs For Sm-oscsmentioning
confidence: 99%
“…Use of femtosecond transient absorption measurements allowed the authors [116] to characterize the kinetics of the charge separation and the recombination in the photoexcited samples of the mentioned phthalocyaninecontaining dyads and evaluate the effect of the central It is seen from the data of this section that porphyrin/ phthalocyanine complexes with a highly charged central atom as these with two charged M 2+ are available satisfy all requirements for organic solar cells. This refers to the wide UV-visible absorption of both a macrocyclic donor and a fullerene-containing acceptor, chemical/photochemical stability, ability to photoinduced charge separation, solubility, solution processability, and stabile/ reproductive photoelectrochemical characteristics.…”
Section: The Relevance Of Mpxs For Sm-oscsmentioning
confidence: 99%
See 3 more Smart Citations